Assessment of blasted surfaces: progress report no. 2 - Pamdeth, N. M.; Apps, R. L. (College of Aeronautics, 1964)
Introduction Previous work had shown that the conditions of grit blasting markedly affected the reflectivity of a mild steel surface and that measurement of reflectivity thus offered a method for the assessment of blasted surfaces. The increase in reflectivity of a series of blasted specimens was found to relate to decreasing surface quality and, after metal spraying, to decreasing bond strength between the base and the sprayed metal. However, one series of specimens did not show any correlation between reflectivity and surface quality and it was decided that an examination of a considerable number of specimens prepared under more carefully controlled conditions was necessary for the next stage of the work. The present report gives the results of reflectivity and bond strength measurements on some 300 specimens of mild steel blasted under a number of different conditions by three suppliers. Reflectivity measurements again showed 'that specimens prepared by any one supplier could be placed in a series of increasing reflectivity, although some difficulties were still encountered in relating the result of different suppliers. These difficulties were most marked with specimens blasted with worn grit. However, correlation between reflectivity, pull-off strength and blasting conditions was good with the series of specimens provided by two suppliers. The series from a third supplier has not been fully tested yet, but very little difference in reflectivity readings has been found.